DEVELOPMENT OF THE SOFTWARE STRUCTURE OF THE CONTROL SYSTEM FOR THE COPPER SULPHATE PRODUCTION PROCESS IN THE SCADA SOFTWARE ENVIRONMENT - HUZ, HANNA; LEVCHUK, IHOR; DUBOVYK, TETYANA; ROMANCHUK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The purpose of this work is to create a software structure of the copper sulfate production process control system in the SCADA environment, consisting of a system of information channels and internal variables that ensure the operation of the human-machine interface and allow the operator to be informed about the course of the technological process, observe the values of all target technological parameters in real time in digital and graphical form, and make it possible to manually control the process and configure control algorithms.The article presents the general software structure of the developed copper sulfate production process control system, which is implemented on the basis of a computer model of the process created in the software environment of the universal modeling program CHEMCAD. OPC technology is used to exchange information in real time between the computer model of the process and the control system. The main stages and features of creating and configuring the information channel system and the internal process control system in the SCADA software environment of the TRACE-MODE system are considered, namely: the characteristics of the proposed software structure are given, the functional purpose of the main input and output information channels of the control system, which are used to ensure information exchange with the OPC server, are determined; a list, functional purpose and characteristics of SCADA system variables are provided, which ensure real-time information exchange between system components (information channels, HMI, control subsystem algorithms). The operability of the proposed software structure and the human-machine interface of the SCADA-based control system for the process of obtaining copper sulfate are checked, transient characteristics of the process are obtained, the reliability of which is verified by comparison with data from a real laboratory installation. The technical solutions, principles and features of the development of the software structure of the control system for the copper sulfate production process proposed in the work are universal in nature and can be used to develop or improve control systems for similar technological processes that are built on the basis of SCADA and mathematical or computer models.
Keywords: control system; human-machine interface; SCADA; copper sulfate